Epidemiology of valvular heart diseases in Africa - Nkomo, Vuyisile T. (SA Heart Journal, 2017)
Rheumatic heart disease (RHD) resulting from rheumatic fever (RF) is the main form of valve disease in Africa. Other forms of valve diseases such as myxomatous mitral valve disease, age-related valve disease, sub-valvular aneurysms or valve disease related to endomyocardial fibrosis are less common than RHD. In developed countries, RF and RHD are rare and no longer pose a public health problem, but the combination of poverty, lack of awareness, lack of infrastructure and resources, and social instability contribute to the persistence of RF and RHD in Africa. The presence of other major infectious diseases also shifts attention away from RF and RHD. Contemporary population-based epidemiologic data utilising echocardiography to detect valve disease suggests the prevalence of valve diseases in Africa is likely much higher than previously thought, meaning the estimated mortality, morbidity and socio-economic burden they cause could also be much higher than currently appreciated. Increased efforts are needed to define the scope of the problem of valve diseases in Africa to draw attention to these illnesses and step up public health efforts to control and eradicate them as has already been achieved in other parts of the world. This article highlights the public health problem of valve diseases in Africa, the efforts underway to combat them and the attendant challenges.